PENGENALAN MICROSOFT OFFICE DALAM PEMBELAJARAN SEKOLAH UNTUK SISWA/I SMP NURUL IMAN CILEDUG - Achmad Khairico; Arsa Raihan Manika; Fikri Ahmad Saputri; Gousul Alam; Rian Nugraha; Ridho Ihsan Rahmatullah; Shakina Putri Syifani; Syayid Umam Hidayah; Tegar Pajar Nugraha; Octaviana Anugrah Ade Purnama (Abdi Jurnal Publikasi, 2023)
Microsoft Office applications are very important to use in digital documentation, whether in the form of text, numbers and presentations. With its use becoming increasingly popular among various groups, both the office sector and the world of education. The development of Microsoft Office applications every year makes it difficult for users to keep up with developments. For this reason, training activities were created in the context of community service, which aims to increase users' knowledge and understanding in using Microsoft Office, especially Microsoft Word, which can be used or implemented in teaching and learning activities and managing documentation. Based on the training that was given and carried out, the results obtained showed that the participants were very enthusiastic, as evidenced by the participants being active in asking questions and discussing the material with the presenters. This counseling is very useful and useful for users to develop the learning process about Microsoft Office.